Investment Potential of Insurance Companies: Ukrainian and European Experience - Liutyi Ihor O.; Lialkin Oleksandr S. (Problemi Ekonomiki)
The article examines the investment potential of insurance companies as a factor in stabilizing the country’s financial system. The main focus is on analyzing the regulatory requirements in the European Union and the possibilities for their implementation in the insurance market of Ukraine. Insurance companies, especially those engaged in life insurance, are traditionally regarded as powerful institutional investors with substantial financial resources and the ability to undertake long-term investments in the real sector of the economy. It is has been determined that EU insurers invest in the real sector by purchasing corporate bonds, with their share in the structure of their investment portfolios accounting for approximately 25 percent (excluding investments in collective investment companies). In the investment portfolios of European insurance companies, government securities constitute the largest share, while the share of stocks is noticeably low. In Ukraine, both investments in stocks and investments in corporate bonds occupy negligible portions of insurers’ investments. It is underscored that regulatory requirements may act as one of the factors shaping an insurer’s investment strategy. In European Union countries, regulatory requirements for calculating solvency capital are defined in Directive 2009/138/EC (Solvency II) and Regulation (EU) No. 2015/35. The market risk module, as part of solvency capital, includes such risk sub-modules as interest rate risk, equity risk, spread risk, property risk, currency risk, and market concentration risk. The article notes that the European Commission has introduced a number of innovations related to the modification of certain solvency capital requirements in order to encourage insurers to invest into the real sector of the economy. In particular, they concerned the reduction of solvency capital requirement levels for investments such as investments in infrastructure projects; investments in unlisted equity; long-term equity investments. The article provides an assessment of the efficiency of such innovations. It is concluded that the experience of implementing such innovations may be relevant for implementation in Ukraine, considering that by 2027, some Ukrainian insurance companies will calculate their solvency capital according to rules harmonized with Solvency II.